A rapid method of whole cell sample preparation for scanning electron microscopy using neodymium chloride. (September 2019) - Novikov, Ivan; Subbot, Anastasia; Turenok, Andrey; Mayanskiy, Nikolay; Chebotar, Igor
Highlights: A new method of cell preparation for SEM using neodymium chloride was suggested. The suggested method does not require fixation, dehydration, and metallization of samples. The method visualizes principal structures of eukaryotic cells, bacteria and fungi. Abstract: The quality of electron microscopy (EM) visualization of biological objects is constantly improving, primarily with the usage of more complex technologies, such as serial block-face scanning electron microscopy (SEM), focused ion beam scanning electron microscopy, and array tomography. Here we suggest a new rapid method of whole cell sample preparation for scanning EM using neodymium chloride treatment followed by staining with lead acetate. This variant of sample preparation does not require separate fixation, complete dehydration, and metal sputtering. By means of SEM in the back-scattered electron mode, in the neodymium-treated preparations, we visualized various morphological structures in human cells (nuclei with nucleoli, cytoskeleton, mitochondria) and microbial cells (Staphylococcus epidermidis, Streptococcus pneumoniae, Escherichia coli, and Candida albicans) preserving their species-specific shape and size. Thus, the suggested method provides additional information combining capabilities of SEM in visualizing cellular surface and transmission EM in detecting intracellular structures. Moreover, biological sample preparation with neodymium and lead is fast, informative, and cost-saving indicating a potential for its practical use for environmental SEM, and can be effectively combined with optical microscopy.